Cross-link in norbornadiene-based polymers from ring-opening metathesis polymerization with pyrrolidine-based Ru complex - Fonseca, Larissa R.; Silva Sá, José L.; Carvalho, Valdemiro P. [UNESP]; Lima-Neto, Benedito S. (Springer Nature, 2018)
Ring-opening metathesis polymerization (ROMP) of norbornadiene (NBD) with [RuCl2(PPh3)2(pyrrolidine)] as the starting complex was evaluated as a function of reaction time, solvent volume, and atmosphere type at 25 °C. Quantitative yields of polyNBD were obtained either under inert argon atmosphere or in air, with 2 mL of CHCl3, for 30 min. Copolymerization of NBD with norbornene (NBE) resulted in 100–70% yield under argon, depending on the NBE/NBD molar ratio, and in 70% yield in air, with 2 mL, for 120 min. TGA, DSC, and DMA measurements and swelling tests supported the occurrence of cross-linking in homopolyNBD and in the copolymers isolated from polymers. SEM micrographs showed porous polymeric NBD materials with pores that decreased in size when increasing the amount of NBD in the starting reaction composition. Results from amine parent complexes when the amine was piperidine or perhydroazepine are also discussed, with high cross-linking degree from reaction with the pyrrolidine complex.
Keywords: Ancillary ligand; Non-carbene complexes; Norbornadiene; Norbornene; ROMP; Ruthenium